ADAPTASI NILAI-NILAI BUDAYA MASYARAKAT MIGRAN PERMANEN DENGAN MASYARAKAT LOKAL DI KECAMATAN TAMPAKSIRING KABUPATEN GIANYAR - Elbert Adinugraha Christianto, Anthony; Naryoso, Agus; Rahardjo, Turnomo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Each person carries cultural values that are inherent to them and will take them wherever they go, including when they migrate to new areas with different cultures. On the other hand, Tampaksiring District is known for its deeply rooted cultural values, which are implemented in the social and religious life of the community. The purpose of this study is to analyze how the cultural values adaptation process occurs between permanent migrant communities and local communities in Tampaksiring District, Gianyar Regency. The theories used include Adaptation Theory, Communication Accommodation, Acculturation, Conflict, and Ethnocentrism. This study uses an interpretive paradigm with a phenomenological approach and data collection techniques involving in-depth interviews with six individuals. The results of the study indicate that aligning cultural values through adaptation and communication processes is crucial for creating harmony and avoiding conflicts in multicultural communities. Challenges faced by permanent migrant communities include discrimination, value clashes, and pressure to maintain their original cultural identity in an environment that may not be supportive. However, an appropriate adaptation process can enhance social harmony. Intercultural conflicts are often triggered by ethnocentrism and cultural value discrepancies, but familial approaches and mediation have proven in resolving these conflicts. The study concludes that intercultural communication, openness to differences, and mutual respect are key for permanent migrant communities and local communities to adapt to differing cultural values. For future research, the author hopes that subsequent studies will discover strategies or ways to enhance social familiarity within communities. Social familiarity is essential for creating strong social integration, which ultimately reduces tensions and conflicts that may arise from cultural differences.